An innovative approach in the synthesis of solid acid catalyst from sugarcane bagasse for the esterification of oleic acid and methanol. (February 2022) - Go, Alchris Woo; Xiao, Yi Chang; Quijote, Kristelle L.; Gunarto, Chintya; Alivio, Roxanne Kathlyn O.; Ju, Yi-Hsu; Angkawijaya, Artik Elisa; Santoso, Shella Permatasari
Abstract: Sugarcane bagasse (SCB) generated in the commercial sector would need to have means to convert the low-cost material into a high-value product(s). One possible high-value product is a solid acid catalyst (SAC) derived from SCB for possible applications in biodiesel production. In this study, a new approach and concept to simultaneously carbonize and sulfonate SCB under less severe conditions, while also recovering available sugars in SCB in the form of sugar-rich hydrolysates were explored. The approach involved a 2-h dilute acid hydrolysis (DAH) step with dilute H2 SO4 (4 wt%) at 100 °C, as pre-treatment to recover about 73% of the available sugars in the hydrolysate. The post-hydrolysis SCB (PHSCB) left after the DAH along with the residual acids were then subjected to drying at 100–150 °C for 12–36 h, to induce simultaneous partial carbonization and sulfonation. The process was successfully carried out and enables the synthesis of carbonized and functionalized PHSCB. The catalyst was successfully used in the esterification of oleic acid and methanol while achieving a conversion of up to 95%. Other process parameters including the influence of solvent-to-oil ratio, catalyst loading, temperature, as well as reusability of the synthesized catalyst were also investigated. Highlights: Dilute acid hydrolysis of sugarcane bagasse (SCB) from a commercial source. The use of DAH to produce hydrolysates rich in reducing sugars (48 g/L). Wet residues from DAH as starting material for solid acid catalyst (SAC) synthesis. Drying of wet SCB with residual acid resulted in carbonization and sulfonation. Synthesized SAC can be used in the esterification of oleic acid with methanol.